Nanoprobe as well as preparation method and application thereof
By using nanoprobes prepared in combination with positively charged conjugated polymers and multi-hydrogen bond donor compounds, the problems of poor selectivity and low detection sensitivity of existing formaldehyde detection probes are solved, and formaldehyde detection with high selectivity, high stability and high sensitivity are achieved, which is suitable for formaldehyde detection in vitro and in vitro.
Patent Information
- Application Number
- CN202411581031.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-03-11
AI Technical Summary
Existing formaldehyde detection probes have problems such as poor selectivity, low detection sensitivity, poor stability, short detection life and high pollution hazards, making it difficult to accurately detect the formaldehyde content in the environment and in the human body.
Nanoprobes were prepared by composited with positively charged conjugated polymers with multi-hydrogen bond donor compounds, fluorescence response was achieved through π-π bond conjugation system and nitrogen positive ions, and fluorescence changes were generated by reaction of multi-hydrogen bonded compounds with formaldehyde to detect formaldehyde concentration.
It realizes formaldehyde detection with high selectivity, high stability and high sensitivity, has good bioaffinity and imaging signal-to-noise ratio, and can show excellent imaging capabilities and detection stability in cell confocal fluorescence imaging.
Smart Images

Figure CN119587722A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biological nanomaterials, and in particular to a nanoprobe and a preparation method and application thereof. Background Art
[0002] Formaldehyde, with the chemical formula HCHO, is an organic compound with a pungent odor. At room temperature, formaldehyde is a colorless, transparent liquid with strong irritation and corrosiveness. Formaldehyde is widely used in manufacturing industries such as building materials, furniture, decoration, and textiles. Therefore, people will inevitably come into contact with formaldehyde in their lives. However, formaldehyde is seriously harmful to human health. Long-term exposure to high concentrations of formaldehyde gas can cause irritation of the eyes, respiratory tract, and skin, and symptoms such as pain, tears, coughing, and skin inflammation. In severe cases, it can even cause suffocation. Formaldehyde is a potential carcinogen. People who are exposed to formaldehyde gas for a long time, especially those engaged in industries related to formaldehyde production, processing, and use, have a higher risk of cancer. Studies have found that formaldehyde is closely related to the occurrence of various cancers such as nasopharyngeal carcinoma, lung cancer, and bladder cancer. In addition, formaldehyde also has serious embryonic developmental toxicity. Pregnant women who are exposed to formaldehyde gas for a long time may suffer from fetal malformations, low body weight, intellectual disabilities, and other problems. Children and adolescents are more sensitive to formaldehyde due to their physical development stage. Long-term exposure to formaldehyde may lead to problems such as decreased immunity, memory loss, and lack of concentration. Therefore, how to accurately detect the formaldehyde content in the environment and the human body is a very meaningful research direction.
[0003] In order to reduce the harm of formaldehyde to humans, my country and many other countries have formulated strict standards and regulations to limit the use of formaldehyde in building materials, furniture, decoration, textiles and other products. At the same time, it is necessary to raise public awareness of the harm of formaldehyde and strengthen indoor environmental testing and management. Therefore, the development of an in vivo and in vitro formaldehyde detection probe is of great significance for protecting human health.
[0004] Although currently commercialized formaldehyde detection probes can quantify or qualify the presence of formaldehyde through different chemical or optical reactions, they still have problems such as poor selectivity, low detection sensitivity, poor stability, short detection life, great pollution hazards, and poor biological affinity.
[0005] Therefore, it is of great significance to develop a formaldehyde detection probe with high sensitivity, high selectivity, high stability, good biological affinity, and good imaging signal-to-noise ratio. Summary of the invention
[0006] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the first aspect of the present invention provides a nanoprobe, which can detect formaldehyde in vivo and in vitro. The nanoprobe has high fluorescence intensity, large Stokes shift, good bioaffinity, and accurate formaldehyde detection ability; it shows excellent imaging ability and formaldehyde detection stability in cell confocal fluorescence imaging.
[0007] The second aspect of the present invention also provides a method for preparing a nanoprobe.
[0008] The third aspect of the present invention further proposes an application of a nanoprobe.
[0009] A nanoprobe according to the first aspect of the present invention comprises a conjugated polymer and a multi-hydrogen bond donor compound; the multi-hydrogen bond donor compound is wrapped inside the conjugated polymer;
[0010] The structural formula of the conjugated polymer is shown in formula (I):
[0011] Where n is 5 to 50.
[0012] The nanoprobe according to the embodiment of the present invention has at least the following beneficial effects:
[0013] The nanoprobe provided by the present invention has high selectivity, high stability, high detection sensitivity and high biological affinity.
[0014] The nanoprobe of the present invention is composed of a positively charged conjugated polymer and a multi-hydrogen bond donor compound. The conjugated polymer has a fluorescence-responsive π-π bond conjugated system and nitrogen cations. The multi-hydrogen bond donor compound can be tightly combined with the conjugated polymer to form stable nanoparticles. The multi-hydrogen bond compound in the nanoparticles can react with formaldehyde to produce fluorescence changes.
[0015] According to some embodiments of the present invention, the average particle size of the nanoprobes is 50-300 nm.
[0016] According to some embodiments of the present invention, the multi-hydrogen bond donor compound refers to a compound having two or more donor molecules capable of providing hydrogen bonds in its molecular structure.
[0017] According to some embodiments of the present invention, the multi-hydrogen bond donor compound includes at least one of ethylenediamine, ethylene glycol, ethylene glycolamine, glyoxal, glycerol, propylenetriamine, D-glucosamine, methyl carbamate, 1-amino-2-methyl-2-propanol or N-methylglycine.
[0018] According to some embodiments of the present invention, the molar ratio of the conjugated polymer to the multi-hydrogen bond donor compound is (2-3):1.
[0019] According to some embodiments of the present invention, the number average molecular weight of the conjugated polymer is 10,000 to 300,000 Da.
[0020] According to the second aspect of the present invention, a method for preparing a nanoprobe is provided, comprising the following steps:
[0021] The conjugated polymer, the multi-hydrogen bond donor compound and the solvent are mixed and stirred, and after the stirring is completed, the nanoprobe is obtained by dialyzing and filtering.
[0022] According to some embodiments of the present invention, the stirring time is 0.5 to 3 hours.
[0023] According to some embodiments of the present invention, the pore size of the dialysis bag used for dialysis is 1000-20000 Da.
[0024] According to some embodiments of the present invention, the particle size of the filter membrane used for filtration is 0.22 μm.
[0025] The third aspect of the present invention provides an application of the nanoprobe described in the first aspect of the present invention in detecting formaldehyde.
[0026] According to some embodiments of the present invention, the nanoprobe is used to detect formaldehyde in living cells by fluorescence imaging.
[0027] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:
[0029] Figure 1 This is the H NMR spectrum of the conjugated polymer I prepared in the embodiment of the present invention;
[0030] Figure 2 This is a schematic diagram of preparing a nanoprobe according to Example 1 of the present invention;
[0031] Figure 3 The particle size distribution diagram of the nanoprobe prepared in Example 1 of the present invention in different solvents;
[0032] Figure 4 The particle size distribution diagram of the nanoprobe prepared in Example 2 of the present invention in different solvents;
[0033] Figure 5 The ultraviolet absorption spectrum and fluorescence spectrum of the nanoprobe prepared in Example 1 of the present invention;
[0034] Figure 6The ultraviolet absorption spectrum and fluorescence spectrum of the nanoprobe prepared in Example 2 of the present invention;
[0035] Figure 7 This is a cytotoxicity graph of the nanoprobe prepared in Example 1 of the present invention;
[0036] Figure 8 This is a cytotoxicity graph of the nanoprobe prepared in Example 2 of the present invention;
[0037] Fig. 9 This is a laser confocal imaging image of Hela cell formaldehyde detection and lysosome staining of the nanoprobe prepared in Example 1 of the present invention;
[0038] Fig.10 This is a laser confocal imaging image of Hela cell formaldehyde detection and lysosome staining of the nanoprobe prepared in Example 2 of the present invention;
[0039] Fig.11 is a selectivity diagram of the nanoprobe of Example 2 of the present invention;
[0040] Fig.12 It is a relationship diagram of the formaldehyde concentration and fluorescence intensity of PFOPMEA of the present invention. DETAILED DESCRIPTION
[0041] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.
[0042] In the description of the present invention, it should be understood that descriptions involving orientations, such as up, down, front, back, left, right, etc., and orientations or positional relationships indicated are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.
[0043] In the description of the present invention, "several" means more than one, "many" means more than two, "greater than", "less than", "exceed", etc. are understood to exclude the number itself, and "above", "below", "within", etc. are understood to include the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing the technical features, and cannot be understood as indicating or implying the relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.
[0044] In the description of the present invention, unless otherwise clearly defined, terms such as setting, installing, connecting, etc. should be understood in a broad sense, and technicians in the relevant technical field can reasonably determine the specific meanings of the above terms in the present invention based on the specific content of the technical solution.
[0045] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0046] The synthetic route and preparation steps of the conjugated polymer used in the embodiments of the present invention are as follows:
[0047]
[0048] A 250 mL round-bottom flask containing hydroquinone (2.21 g, 20 mmol), 1,6-dibromohexane (7.38 mL, 48 mmol), potassium carbonate (1.38 g, 10 mmol) and 1,4-dioxane (100 mL) was heated to 80 ° C for 24 hours. The mixture was then diluted with 200 mL DCM, washed with saturated sodium bicarbonate, extracted with water and DCM, dried with anhydrous magnesium sulfate, and concentrated under reduced pressure to provide a crude product. Further purification by flash column chromatography (hexane: DCM = 6: 1) gave 7.12 g (yield 82%) of the intermediate product (1,4-bis ((6-bromohexyl) oxy) benzene) as a yellow solid.
[0049] A 100 mL tube containing 1,4-bis((6-bromohexyl)oxy)benzene (7.12 g, 16.4 mmol) and Et3N (30 mL) was kept at 120° C. for 24 hours. The reaction mixture was then washed with ethyl acetate to give a white solid 5,5′-(1,4-phenylenebis(oxy))bis(N,N,N-triethylpentan-1-ammonium) bromide product (9.39 g, yield: 90%).
[0050] A tube containing 2,7-dibromo-9-fluorenone (0.0518 g, 0.2 mmol), 5,5'-(1,4-phenylenebis(oxy))bis(N,N,N-triethylpentane-1-ammonium) bromide (0.153 g, 0.24 mmol), palladium acetate (0.0023 g, 0.01 mmol), potassium carbonate (0.1104 g, 0.8 mmol), pivalic acid (0.02 g, 0.2 mmol) and 1 mL of toluene was heated to 150°C under nitrogen atmosphere for 36 hours. The final product, conjugated polymer I (0.148 g, 0.175 mmol, yield: 91%, Mn=26380 Da), was then purified by dialysis using a 10 kDa molecular weight semipermeable membrane and dried to obtain a yellow solid.
[0051] Structural identification of conjugated polymer Ⅰ:
[0052] 1 H NMR spectrum Figure 1 As shown, the nuclear magnetic resonance hydrogen spectrum and carbon spectrum data are as follows:
[0053] 1 H NMR (400MHz, MeOD) δ6.91(d,J=6.1Hz,4H),4.68–4.47(m,2H),4.06–3.96(m,2H),3.84-3.41(m,16H),2.05–1.78(m,8H),1.69-1.31(m,18H).
[0054] 13 C NMR (101MHz, MeOD) δ153.34,115.35,115.28,115.26,115.22,70.39,68.43,68.11,66.74,56.83,52.70,28.92,25.90,25.46,21.39,6.70.
[0055] Example 1
[0056] This example provides a nanoprobe, and its preparation schematic diagram is as follows Figure 2 As shown, the preparation method is as follows:
[0057] Take the aqueous solution of conjugated polymer I (60μL, 50mM) in a glass reactor, add a magnetic particle, add 3mL ultrapure water, then use a 1mL sterile needle syringe to absorb ethanolamine (90μL, 1.5mmol), stir and react for 2h to obtain a crude formaldehyde detection nanoparticle probe aqueous solution. Select a semipermeable membrane with a molecular weight of 20000Da to dialysis and purify the above crude product. Add a magnetic particle to the semipermeable membrane containing the nanoparticle aqueous solution in a 2L beaker, add ultrapure water for rotary dialysis, change the water every 4h, and end the dialysis after 24h to obtain a semi-crude nanoparticle aqueous solution. The semi-crude nanoparticle aqueous solution is drawn with a 5mL sterile needle syringe and passed through a 0.22μm needle filter to obtain a nanoprobe (named: PFOPMEA; wherein the molar ratio of conjugated polymer I and ethanolamine is 2:1).
[0058] Example 2
[0059] Take the aqueous solution of conjugated polymer I (60μL, 50mM) in a glass reactor, add a magnetic particle, add 3mL ultrapure water, then use a 1mL sterile needle syringe to absorb ethylenediamine (90μL, 1.5mmol), stir and react for 2h to obtain a crude mitochondrial targeted nanoparticle aqueous solution. Select a semipermeable membrane with a molecular weight of 20000Da to dialysis and purify the above crude product. Add a magnetic particle to the semipermeable membrane containing the nanoparticle aqueous solution in a 2L beaker, add ultrapure water for rotary dialysis, change the water every 4h, and end the dialysis after 24h to obtain a semi-crude nanoparticle aqueous solution. The above semi-crude nanoparticle aqueous solution is drawn with a 5mL sterile needle syringe and passed through a 0.22μm needle filter to obtain a pure nanoprobe (named: PFOPNEn; wherein the molar ratio of conjugated polymer I and ethylenediamine is 2:1).
[0060] Test Example 1 Particle Size Distribution Test
[0061] The nanoparticle probe aqueous solutions prepared in Examples 1 and 2 were dispersed in ultrapure water and PBS, and the particle size distributions of PFOPMEA and PFOPNEn in different environments (ultrapure water and PBS) were measured as follows: Figure 3 and Figure 4 As shown, it can be seen that PFOPMEA and PFOPNEn have good dispersibility and single particle size distribution in different aqueous solutions, and the average particle sizes of PFOPMEA and PFOPNEn are 225nm and 208nm, respectively.
[0062] Test Example 2 Ultraviolet absorption spectrum
[0063] The nanoparticle probe aqueous solutions prepared in Examples 1 and 2 were prepared into 1 mM PBS stock solution, and the mitochondria-targeted nanoparticle probe stock solution was diluted into a 20 μM PBS solution. The ultraviolet absorption values were scanned and the absorption curve was plotted. The ultraviolet absorption spectrum of Example 1 is shown in FIG. Figure 5 , Figure 6 As shown in the figure, Examples 1 and 2 each have two absorption peaks, and the peak values are close to 220nm and 280nm.
[0064] Experimental Example 3 Fluorescence Spectrum
[0065] The nanoprobe aqueous solutions prepared in Examples 1 and 2 were prepared into 1 mM PBS stock solution, and the mitochondria-targeted nanoparticle probe stock solution was diluted into a 20 uM PBS solution, and its fluorescence spectrum was measured to obtain its fluorescence emission curve as shown in FIG. Figure 5 , Figure 6 In the PBS solution, Examples 2 and 3 each have a maximum emission peak, which are 520 nm and 510 nm respectively; it can be seen that Examples 1 and 2 have obvious Stokes shifts, which are 300 nm and 290 nm respectively.
[0066] Test Example 3 CCK-8 Cytotoxicity Test
[0067] Hela cells in the logarithmic growth phase were inoculated in a 96-well plate, with about 10,000 cells in each well, and cultured for 6 hours at 37°C and 5% CO2 using DMEM (H) medium containing 10% fetal bovine serum (FBS) and 1% double-antibody (penicillin-streptomycin, 1000KU / L). After the cells were completely attached, different volume gradients of the nanoparticle PBS solutions of Examples 2 and 3 were added, with 3 replicate wells for each gradient, and a blank control group was also set up. After adding the nanoparticle PBS solution, the culture was continued for 48 hours, and the cell survival rate was detected using a CCK-8 toxicity kit. The results are as follows: Figure 7 and Figure 8 As shown, when a high dose of 25 μL was added, Examples 1 and 2 had only low cytotoxicity to Hela cells, and when the volume was reduced to below 20 μL, the cell survival rate was above 95%.
[0068] Experimental Example 4 Laser Confocal Imaging of Lysosome Staining in Hela Cells
[0069] A certain concentration of Hela cells were cultured overnight in a 35 mm confocal culture dish, and the cells were pretreated with a certain concentration of formaldehyde FA (200 μM or 400 μM) for 1 hour, and then dyed with Example 1 or 2 (1 μL of 1 mM nanoparticle stock solution was added to 1 mL of medium) and LysoTracker Red (1 uL, 50 nM) for 0.5 hours. The dye was imaged under a laser confocal microscope using 100% intensity excitation light and emission filters. The results are shown in FIG. Fig. 9 and Fig.10 As shown. Since the multi-hydrogen bond small molecules in the nanoprobe react with FA, the nanoprobe structure is destroyed and the fluorescence is weakened, so the nanoprobe can detect formaldehyde concentration at the cellular level and observe it through a fluorescence microscope. In addition, the conjugated polymer in the nanoprobe has a large Stokes shift and high biological affinity, which makes it have the advantages of low background fluorescence, good imaging signal-to-noise ratio, and low biological toxicity.
[0070] Experimental Example 5: Stability Test
[0071] PFOPMEA (1 mL, 20 μM) was taken in multiple 1.5 mL centrifuge tubes, and hydrochloric acid or sodium hydroxide was added to adjust the pH to 3.5, 7.4 or 9.6, and then cooled to -20°C or 100°C, respectively, and then converted to room temperature after 4 hours of heat preservation to test the particle size and potential. The results are shown in Table 1. From the results, it can be seen that the particle size of nanoparticle PFOPMEA remains basically unchanged under different acid and alkali and different temperature environments, so its structure has good acid and alkali resistance, high and low temperature stability.
[0072] Table 1. PFOPMEA stability test.
[0073]
[0074] Experimental Example 6 Selectivity Experiment
[0075] Fluorescence emission and UV absorption spectra of 20 μM PFOP-NEt3(+) (conjugated polymer I), PFOPNEn probe, and mixed solution of PFOPNEn and FA were tested. + , K + 、Zn 2+ , Ca 2+ , Cu 2+ , Cl - 、HSO3 2- 、SO4 2- 、HCO3 - and HPO4 2-) and then add 20μM FA. The fluorescence emission spectrum parameters are: excitation light 380nm, slit width 1nm, scanning speed 800nm / min; UV absorption spectrum parameters are: slit width 1nm, scanning speed 500nm / min. The results are as follows Fig.11 As shown; Fig.11 (a) is the fluorescence emission intensity diagram; Fig.11 (b) is the ultraviolet absorption spectrum; Fig.11 (c) is a histogram of ion-selective fluorescence intensity; from the results in the figure, it can be seen that the conjugated polymer I itself has only a relatively weak red fluorescence. After combining with ethanolamine to form nanoparticles PFOPNEn, the fluorescence intensity is greatly enhanced and blue-shifted. After PFOPNEn reacts with FA, the fluorescence intensity drops sharply. In addition, the above-mentioned ions have no obvious interference effect on the detection of FA by the PFOPNEn probe. Only after the addition of FA does the fluorescence intensity of the PFOPNEn probe drop sharply. Therefore, the FOPNEn probe has good detection and selectivity for FA.
[0076] Experimental Example 7 Relationship between formaldehyde concentration and fluorescence intensity
[0077] PFOPMEA probe (2 mL, 500 μM) was placed in a 5 mL reactor, the FA concentration was gradually increased, and the fluorescence intensity of PFOPMEA was detected at the same time. Fluorescence emission spectrum parameters: excitation light 380 nm, slit width 1 nm, scanning speed 800 nm / min. The results are shown in Figure 2. Fig.12 As shown, Fig.12 (a) is the fluorescence spectrum change of PFOPMEA in response to formaldehyde; Fig.12 (b) Response pattern of fluorescence intensity of PFOPMEA to formaldehyde concentration; Fig.12 (c) Yes Fig.12 (b) Linear graph of the fluorescence intensity change pattern fitting. As the concentration of FA increases, the fluorescence intensity of PFOPMEA gradually decreases, and the two are linearly related. When the final FA concentration is about 200 μM, the fluorescence intensity of PFOPMEA decreases to the minimum value. Therefore, PFOPMEA can detect FA concentration by fluorescence intensity changes, and 500 μM PFOPMEA can detect FA in the concentration range of 0-200 μM.
[0078] In summary, the present invention is a composite of a positively charged conjugated polymer and a multi-hydrogen bond compound, wherein the conjugated polymer has a fluorescently responsive π-π bond conjugated system and a nitrogen cation; the multi-hydrogen bond compound can form stable nanoparticles with the polymer; the multi-hydrogen bond compound in the nanoprobe can react with formaldehyde to produce fluorescence changes to detect the formaldehyde concentration; the nanoprobe can perform concentration-dependent detection of formaldehyde; and can perform in vivo and in vitro detection of formaldehyde. The nanoprobe has high fluorescence intensity, large Stokes shift, good bioaffinity, and accurate formaldehyde detection capability; it exhibits excellent imaging capability and formaldehyde detection stability in cell confocal fluorescence imaging. It fills the gap in the current market for in vivo and in vitro formaldehyde detection probes.
[0079] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A nanoprobe, characterized in that: It comprises a conjugated polymer and a multi-hydrogen bond donor compound; the multi-hydrogen bond donor compound is wrapped inside the conjugated polymer; The structural formula of the conjugated polymer is shown in formula (I): Where n is 5 to 50.
2. The nanoprobe according to claim 1, characterized in that The average particle size of the nanoprobe is 50-300 nm.
3. The nanoprobe according to claim 1 or 2, characterized in that: The multi-hydrogen bond donor compound includes at least one of ethylenediamine, ethylene glycol, ethylene glycolamine, glyoxal, glycerol, propylenetriamine, D-glucosamine, methyl carbamate, 1-amino-2-methyl-2-propanol or N-methylglycine.
4. The nanoprobe according to claim 1 or 2, characterized in that: The molar ratio of the conjugated polymer to the multi-hydrogen bond donor compound is (2-3):
1.
5. The nanoprobe according to claim 1 or 2, characterized in that: The number average molecular weight of the conjugated polymer is 10000-300000 Da.
6. The method for preparing a nanoprobe according to any one of claims 1 to 5, characterized in that: The steps include: The conjugated polymer, the multi-hydrogen bond donor compound and the solvent are mixed and stirred, and after the stirring is completed, the nanoprobe is obtained by dialyzing and filtering.
7. The method for preparing a nanoprobe according to claim 6, characterized in that: The stirring time is 0.5 to 3 hours.
8. The method for preparing a nanoprobe according to claim 6, characterized in that: The pore size of the dialysis bag used for dialysis is 1000-20000Da.
9. Use of the nanoprobe according to any one of claims 1 to 5 in detecting formaldehyde.
10. The use according to claim 9, characterized in that: The nanoprobe is used to detect formaldehyde in living cells through fluorescence imaging.